Medallion „Librarians in time and space”. Nikolai Rubakin (Confluenţe Bibliologice, 2025)
The article outlines the portrait of Nikolai Rubakin, a prominent figure in the history of Russian culture and librarianship. Rubakin was a writer, bibliographer, psychologist, and passionate promoter of reading and self-education, considering the library an active space for intellectual formation. Author of over 280 books and initiator of the theory of bibliopsychology, he promoted the idea of a deep relationship between the reader and the book. His modern concepts regarding the organization of libraries and the psychological classification of reading have decisively influenced the development of bibliology. The paper emphasizes Rubakin's vast intellectual legacy and his humanistic vision of the book as an instrument of emancipation.